Unusual magnetotransport properties in a FeAs single crystal - Khim, Seunghyun; Gillig, Matthias; Klingeler, Rüdiger; Wurmehl, Sabine; Büchner, Bernd; Hess, Christian (Physical review, 2016)
We have investigated the magnetoresistance (MR) and Hall resistivity properties of a FeAs single crystal which exhibits magnetic order below TN = 69 K. We observe nonlinear Hall resistivity and linear MR in the presence of magnetic-order-connected Fermi surface reconstruction. The analysis of the magnetotransport data using a two-carrier model suggests the emergence of an additional minor hole Fermi surface which coexists with major electron carriers below TN. The origin of the linear MR, however, remains inconsistent with current explanations based on the electronic band structure, i.e., the quantum linear MR model from linearly dispersive Dirac cones and linear MR as a result from strong velocity changes of the cyclotron motion near nested Fermi surfaces. While a macroscopic inhomogeneity in a mobility distribution may cause the linear MR as widely observed in other semimetals with high mobilities, the spiral magnetic order of FeAs seems to ask for an alternative description which takes the specific magnetic order and details of the electronic structure of FeAs as well as a possible entanglement between them into account.